ASSOCIATION OF BODY MASS INDEX AND DIETARY COMPLIANCE ON GLYCEMIC CONTROL AMONG OUTPATIENTS WITH TYPE 2 DIABETES MELLITUS IN KUALA TERENGGANU - Khoder, Nurul Husna Binti; Harith, Sakinah Binti; Mufidah, Indahtul (Universitas Darussalam Gontor, 2025)
Background: Glycemic control is essential in managing Type 2 diabetes and preventing complications. Several factors, including sociodemographic characteristics, BMI, and dietary compliance, may influence glycemic outcomes. This study aimed to identify key factors associated with glycemic control among Type 2 diabetic outpatients in Kuala Terengganu. Methods: A retrospective study was conducted involving 134 outpatients from one clinic and one hospital, selected through purposive sampling. Data were collected via patient records and questionnaires. Glycemic control was assessed using HbA1c levels, with compliance measured based on self-reported dietary behavior. Results: Among all sociodemographic variables, only the type of treatment (diet and oral anti-diabetic drugs) showed a significant association with glycemic control (p = 0.013). Additionally, BMI was significantly associated with glycemic outcomes (p = 0.029), as poor glycemic control was more prevalent among overweight (84.2%) and obese (82.7%) individuals. No significant association was found between dietary compliance and glycemic control (p = 0.560), potentially due to reporting bias or inconsistent adherence. Conclusion: BMI and treatment type are significant factors influencing glycemic control in this population. Despite no observed link between dietary compliance and glycemic control, further studies with larger, more diverse samples are needed. Healthcare providers should focus on improving BMI and treatment awareness to enhance diabetes management. Keywords: Glycemic control, Type 2 diabetes, BMI, Dietary compliance, Sociodemographic factors, Kuala Terengganu